Expression of TNF-α and Related Signaling Molecules in the Peripheral Blood Mononuclear Cells of Rheumatoid Arthritis Patients - Sunil Kumar Raghav; Bhawna Gupta; Charu Agrawal; Ved P. Chaturvedi; Hasi R. Das (Hindawi Limited, 2006)
We examined the role of tumor necrosis factor (TNF-α) and its related signaling intermediates leading to apoptosis/proliferation in the peripheral blood mononuclear cells (PBMCs) of RA patients. The constitutive expression of mRNA for TNF-α receptors (TNFR-I and TNFR-II) and the adapter molecules, such as the TNF receptor-associated death domain protein (TRADD), Fas-associated death domain protein (FADD), receptor interacting protein (RIP), and TNF receptor-associated factor 2 (TRAF-2) were analyzed by reverse transcriptase-PCR (RT-PCR) in PBMCs from control and RA cases. PBMCs of RA patients showed a significant increase in TNF-α and TNFR-I expression as compared with that from control subjects along with significantly increased constitutive expression of TRADD, RIP, and TRAF-2 mRNA. There was a decrease in expression of FADD in RA patients, but the difference was not significant as compared to controls. These data suggested enhanced signaling by the TNFR-I-TRADD-RIP-TRAF-2 pathway and suppressed signaling by the TNFR-I-TRADD-FADD pathway in PBMCs of RA patients. However, the regulatory mechanisms for TNF-α induced signaling may not be explained only by these pathways.